Neuropathic causes of groin pain in athletes: understanding nerve involvement - Zarko Vuckovic (17052435) (2025)
Purpose Groin pain in athletes, particularly inguinal-related groin pain, remains a diagnostic and therapeutic challenge despite recent consensus on terminology. This study aims to explore nerve disorders as a key contributor to groin pain in athletes, focusing on the anatomy, aetiology, diagnosis, and management options. Methods A comprehensive review of the literature was conducted, focusing on the anatomical variability of the ilioinguinal, iliohypogastric, and genital branch of the genitofemoral nerves, clinical presentations, diagnostic methods, and conservative and surgical treatments for nerve-related inguinal pain. Key studies on nerve entrapment, neuropathic and nociceptive pain mechanisms, and surgical outcomes were analyzed. Results Variability in nerve pathways and sensory overlap complicate diagnosis and management. Neuropathic pain often presents with burning or electric sensations due to nerve compression or entrapment, while nociceptive pain manifests as dull or stabbing pain. Conservative treatment, including exercise-based rehabilitation and nerve blocks, offers relief in many cases. For refractory cases, surgical treatment can provide significant pain resolution, with nerve identification and potential neurectomy improving outcomes. Conclusion Nerve disorders play a critical role in inguinal-related groin pain in athletes. Accurate diagnosis relies on detailed clinical examination and targeted imaging. Conservative treatments are first line, but surgical interventions addressing nerve entrapment or compression are effective for persistent cases. Future research should focus on the role of collagen deficiencies, nerve histopathology, and long-term outcomes of different treatment modalities. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00264-025-06461-z